Associations of Education Level With Survival Outcomes and Treatment Receipt in Patients With Gastric Adenocarcinoma - Xu, Jiaxuan; Du, Shuhui; Dong, Xiaoqing (Frontiers in Public Health, 2022)
Background It remains largely unclear how education level, an important socioeconomic factor, affects prognoses for patients with gastric adenocarcinoma (GAC). We aimed to demonstrate the associations between education level and clinical outcomes in patients with GAC. Methods We included a total of 30,409 patients diagnosed with GAC from the Surveillance, Epidemiology, and End Results 18 registry database. Education level, household income, unemployment rate, poverty rate, insurance status, and marital status were selected as sociodemographic variables for the comprehensive analysis. Cox and logistic regression models, Kaplan–Meier curves, and subgroup analyses were the primary statistical methods employed. Results A low level of education was correlated with less income, higher unemployment rates, and higher poverty rates (all p < 0.001). The multivariate Cox analysis indicated that a high education level was significantly associated with superior overall survival rates and cancer-specific survival rates in patients with GAC (both p < 0.001). We also corroborated favorable survival outcomes by high education level within almost every clinical and demographic subgroup. Furthermore, chemotherapy combined with surgery could markedly prolong the survival for all patients, including patients of stage IV cancer (both p < 0.001). By using multivariable logistic models, patients in counties with high education levels had a higher probability of chemotherapy receipt (p < 0.001). Contrarily, those in the counties with low levels of education were less likely to receive chemotherapy or undergo surgery (p < 0.001). Conclusions Education level was identified and confirmed as an independent predictor of treatment and survival for GAC patients. Efforts are needed to provide effective interventions for those whose educational status is adverse.